Sistemas de produção consorciados de palma forrageira e cunhã sob regimes de sequeiro e irrigado com água salobra no semiárido - Ribeiro, Rute Maria Rocha (2023)
Irrigation (full or supplemental) can reduce losses from rainfed agriculture even when brackish waters are used. Furthermore, the cultivation of forage crops adapted to semi-arid regions with low water requirements can enable greater profitability in agricultural activities in the Brazilian semi-arid region. The use of brackish waters in irrigation or supplementation of forages with low water demands can increase forage production and efficient use of water in these regions. In this context, the objective of the present study was to evaluate the effect of irrigation with brackish water and different water scenarios and biomass production systems on productivity, protein accumulation, water use efficiency, mineral element content, physiological responses and crop morphology. forage cactus and butterfly pea. The experiment was conducted in the municipality of General Sampaio – CE, in the years 2022 and 2023. The experimental design was in randomized blocks, in subdivided plots, with four blocks. The plots referred to two water scenarios: rainfed and irrigated; the subplots were formed by four production systems composed of the forage plants butterfly pea (Clitória ternatea L.) and forage cactus (Opuntia stricta (Haw) Haw): System 1 – forage cactus in monoculture (P) (2,0 x 0,1m); System 2 – butterfly pea in monoculture (C) (1,0 x 0,1m); System 3 – intercropped forage cactus (2,0 x 0,1m) with a butterfly pea line (P+1C) (1,0 x 0,1m); System 4 – forage cactus (3,0 x 0,1m) combined with two butterfly pea lines (P+2C) (1,0 x 0,1m). During the study, the average salinity value of irrigation water (1:1 mixture of the two water sources) was 3,0 and 4,0 dS m-1, respectively for the irrigation of butterfly pea and forage cactus. The butterfly pea crop received supplementary irrigation between the months of February and August during the dry spells, while the forage cactus was irrigated only during the dry season (July to December), in a seven-day irrigation shift. During the two years of the study, the following variables were measured: Fresh and dry biomass productivity, seed productivity (butterfly pea), physical water productivity, crude protein productivity, morphophysiological indices (forage cactus), gas exchange (butterfly pea), concentration of mineral elements in plant tissues, soil pH and soil electrical conductivity using the 1:1 method. The use of supplementary irrigation with brackish water during the summer in butterfly pea culture favors greater biomass and seed production, as well as increasing the crude protein content of the system in monoculture, mitigating the effects of water stress on stomatal conductance, photosynthesis, transpiration, internal concentration of CO2, being beneficial to the agronomic performance of Clitória ternatea L. The use of supplementary irrigation with brackish water in intercropped systems generated increases in stomatal conductance and photosynthetic rate and reductions in sodium concentration in butterfly pea plants, which P+2C system when supplemented increased the assimilation of N and P by the crop. Irrigation with brackish water in the dry season in forage cactus cultivation reduces the negative effects of water stress and benefits the production of fresh and dry biomass, crude protein content, physical water productivity and cladode growth, as well as providing higher Na+concentration in cactus cladodes. The P+1C intercropping system in relation to forage cactus monoculture proved to be the most advantageous in terms of growth, biomass production, crude protein and water use efficiency, proving to be an alternative for forage production in the Brazilian semi-arid region. Supplemental or seasonal irrigation with brackish water did not salinize the soil, as the rain allowed the leaching of salts contributed to the soil, posing little risk for sandy soils with good natural drainage, such as the one used in the present study.